Outcomes in hypertrophic obstructive cardiomyopathy patients undergoing non-cardiac surgery-a nationwide analysis. (3rd October 2022) - Victor, V; Abumoawad, A; Ibrahim, F; Barssoum, K
Abstract: Introduction: Patients with hypertrophic obstructive cardiomyopathy (HOCM) have a unique pathophysiological profile that increases their chances of having adverse events in the postoperative period following surgical procedures. Owing to the rarity of the disease, few studies are available for assessing readmission risk in HOCM patients undergoing noncardiac surgical procedures. Purpose: Our study aimed to assess 30-day readmission rates and causes for readmissions among HOCM patients who had undergone noncardiac surgeries in hospitals across the United States (US). Methods: We used appropriate International Classification of Diseases Code, 10th Revision Clinical Modification (ICD-10-CM) codes to identify patients who had been admitted for non-cardiac surgeries between January 2016 and December 2019 based on data from the National Readmissions Database (NRD). The NRD is a publicly available all-payer in-patient database sponsored by the Agency for Healthcare Research and Quality, containing discharge data from approximately 18 million discharges each year, accounting for 61.8% of the total US resident population. Patients were subdivided into two sub-groups based on the presence or absence of HOCM. 30-day readmission rates and causes of readmissions were compared between both groups. STATA version 17 (College Station, TX: StataCorp LLC) was used for statistical analyses. Results: A total of 5, 497, 134 patients out of whom 2, 089 had HOCM were identified and included for analysis. Patients with HOCM had statistically significant higher rates of readmissions for central nervous system related complications such as stroke or transient ischemic attack (TIA), cardiogenic shock, acute heart failure, unspecified iatrogenic cardiac complications, acute kidney injury, sepsis in addition to higher rates of post op respiratory failure, acute myocardial infarction and major adverse cardiovascular and cerebrovascular events (MACCE) during the index admission when compared to the other subgroup. Conclusion: Our study, despite being retrospective in nature, is one of the largest to date assessing readmission risk in HOCM patients undergoing noncardiac surgeries. Similar to previous studies, HOCM patients have higher rates of readmissions and MACCE in the 30-day period following noncardiac surgical procedures. In light of these findings, shared medical decision making and appropriate counseling regarding complications in the postoperative period will be necessary for HOCM patients who undergo noncardiac surgical procedures. Funding Acknowledgement: Type of funding sources: None.